2023
DOI: 10.26434/chemrxiv-2022-w994j-v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxygen-redox activity in non-Li-excess W-doped LiNiO2 cathode

Abstract: The desire to increase the energy density of stoichiometric layered LiTMO2 (TM = 3d transition metal) cathode materials has promoted investigation into their properties at high states of charge. Although there is increasing evidence for pronounced oxygen participation in the charge compensation mechanism, questions remain whether this is true O-redox, as observed in Li-excess cathodes. Through a high-resolution O K-edge resonant inelastic X-ray spectroscopy (RIXS) study of the Mn-free Ni-rich layered oxide, Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 82 publications
(185 reference statements)
1
16
0
Order By: Relevance
“…14,15 Some argue that this reflects the change in covalency of the Ni-O bond with the electron-hole density shifting more towards O than Ni when Ni is highly oxidised, 8,[17][18][19] while others argue O oxidation is invoked. [13][14][15]20 Recent research into O oxidation in Li-rich cathodes, such as Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 , has indicated that oxidised oxygen takes the form of molecular O 2 , which is trapped within vacancy clusters in the cathode structure. [21][22][23][24][25] However, in the case of stoichiometric materials like LiNiO 2 , it has been argued that this same mechanism cannot apply due to the lack of transition metal vacancies in the fully dense transition metal layers (in the Li-rich materials the Li in the transition metal layers are removed on charge and the remaining vacancies cluster to accommodate the O 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15 Some argue that this reflects the change in covalency of the Ni-O bond with the electron-hole density shifting more towards O than Ni when Ni is highly oxidised, 8,[17][18][19] while others argue O oxidation is invoked. [13][14][15]20 Recent research into O oxidation in Li-rich cathodes, such as Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 , has indicated that oxidised oxygen takes the form of molecular O 2 , which is trapped within vacancy clusters in the cathode structure. [21][22][23][24][25] However, in the case of stoichiometric materials like LiNiO 2 , it has been argued that this same mechanism cannot apply due to the lack of transition metal vacancies in the fully dense transition metal layers (in the Li-rich materials the Li in the transition metal layers are removed on charge and the remaining vacancies cluster to accommodate the O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Substantial efforts have been made to understand these phenomena and the structural transitions that take place when Li is extracted from LiNiO 2 , but there remains considerable debate over the extent of Ni oxidation and O-redox in LiNiO 2 , particularly across the voltage plateau at 4.2 V vs. Li + / Li. [13][14][15][16] Despite reaching a composition close to NiO 2 at the end of charge with Ni nominally in the +4 oxidation state, bulk sensitive X-ray absorption spectroscopy (XAS) appears to show incomplete oxidation of Ni 3+ to Ni 4+ when the edge position is compared to other Ni 4+ -containing oxides. 14,15 Some argue that this reflects the change in covalency of the Ni-O bond with the electron-hole density shifting more towards O than Ni when Ni is highly oxidised, 8,[17][18][19] while others argue O oxidation is invoked.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The process in which only the nonbonding O 2p states are involved (one-band redox) is irreversible. Menon et al 24 performed O K-edge X-ray spectroscopy and RIXS measurements on LiNi 0.98 W 0.02 O 2 and demonstrated that the same oxidized oxygen environment (ascribed to trapped molecular O 2 ) exists in both Li-excess and non-Li-excess systems. This shows that the detection of O n− by this method does not correlate to the additional capacity found in Li-excess systems.…”
Section: Introductionmentioning
confidence: 99%